EFFICACY OF FECAL MICROBIOTA TRANSPLANTATION IN TREATING GASTROINTESTINAL DISEASES: A SYSTEMATIC REVIEW OF EVIDENCE IN CDI, UC, IBS, AND CROHN’S DISEASE - Julia Kular,; Oliwia Malec,; Izabella Michalska,; Maciej Karwat,; Mateusz Myśliwiec,; Justyna Niebylecka,; Natalia Glanc,; Tytus Tyralik,; Grzegorz Zalewski,; Dominik Sendecki, (International Journal of Innovative Technologies in Social Science, 2025)
Background: Fecal microbiota transplantation (FMT) has emerged as a novel therapeutic approach for various gastrointestinal disorders characterized by microbiota dysbiosis. While FMT is well established for recurrent Clostridioides difficile infection, its efficacy in conditions such as ulcerative colitis, Crohn’s disease and irritablebowel syndrome remains under investigation.Objective: To systematically review and synthesize current evidence on the efficacy and safety of FMT in treatment of CDI, UC, CD and IBS, focusing on clinical outcomes, microbiota changes and delivery strategies.Methods: This review PRISMA guidelines to assess the efficacy and safety of fecal microbiota transplantation in CDI, UC, CD and IBS. Databases searched included PubMed, Google Scholar. Studies were screened and selected by two reviewers. Data on FMT protocols, clinical outcomes and safety were extracted and analyzed narratively to study heterogenity.Results: FMT shows high cure rates in recurrent CDI with success rates over 80% regardless of delivery method. In UC multi-dose protocols with well-selected donors can induce remmission. Evidence in CD is limited, with some benfits in subgroups like steroid dependent patients. In IBS, results are mixed, colonoscopic FMT appears more effective than capsules, but placebo effects and patient variability complicate interpretation. FMT is generally safe, with mostly mild side effects.Conclusion: FMT is highly effective and well-tolerated therapy for recurrent CDI. It shows potential in treating UC, with emerging evidance in CD and IBS. Efficacy depends on delivery route, donor recipient compatibility and disease specific factors. Standarized protocols and further high-quality trials are needed to clarify FMT’s role across gastrointestinal disorders.